2012
DOI: 10.1109/tip.2011.2167626
|View full text |Cite
|
Sign up to set email alerts
|

A Compressive Sensing and Unmixing Scheme for Hyperspectral Data Processing

Abstract: Hyperspectral data processing typically demands enormous computational resources in terms of storage, computation and I/O throughputs, especially when real-time processing is desired. In this paper, we investigate a lowcomplexity scheme for hyperspectral data compression and reconstruction. In this scheme, compressed hyperspectral data are acquired directly by a device similar to the single-pixel camera [5] based on the principle of compressive sensing. To decode the compressed data, we propose a numerical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Studies have shown that the huge HS datacubes are often highly redundant [13][14][15][16][17] and, therefore, very compressible or sparse. This gives the incentive to implement Compressive Sensing (CS) theory in HS systems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the huge HS datacubes are often highly redundant [13][14][15][16][17] and, therefore, very compressible or sparse. This gives the incentive to implement Compressive Sensing (CS) theory in HS systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the proposed method, we first use a coherent measurement matrix to compressively sense HSI and then use the VCA method to estimate the endmember directly from the HSI observations without recovering the images, which is a necessary step in the traditional method. As shown in the dashed parts in Figure 6 , if the proportion information is required, one can use another incoherent measurement matrix to capture the global information of HSI, which can be used along with the estimated endmembers to recover the proportions [ 5 , 20 ].…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…There are many methods for blind HU such as pixel purity index (PPI) [ 14 ], N-FINDR [ 15 ], vertex component analysis (VCA) [ 16 ], SSCBSS [ 17 ], hypGMCA [ 18 ], and modified VCA (MVCA) [ 19 ], which are all based on the Nyquist sampling theorem. There are also some HU methods based on the CS theory, such as CSU [ 20 ] and the method proposed in [ 5 ], but they all assume that the endmembers are known as side information. Endmember estimation is a key step to identify the materials in HSI, and in many applications, the endmembers are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imaging has increased significantly over the past decade, mainly because of a large amount of reference information, including the complete spectra of ground objects, which enables precise material identification using spectroscopic analysis [5]- [7]. There is a wide range of hyperspectral imaging applications such as terrain classification [8], remote surveillance [2], mineral detection and exploration, environmental monitoring, and military surveillance [9], and pharmaceutical process monitoring and quality control [10]. The main advantage of using hyperspectral imagery is that the spectral signature of each pixel can help identify the materials in the scene [11].…”
Section: Introductionmentioning
confidence: 99%